Hadi DAP, Allies a threat to Islam - Zulkefli, Adie Suri (New Strait Times, 2017)
PAS president Datuk Seri Abdul Hadi Awang yesterday affirmed the party's ulama stand to prevent DAP and its allies from wresting Putrajaya. He said Pas would not allow the DAP-led coalition from winning the 14th General Election (GE14) and forming the federal government because it would impose a threat to the Islamic interest.